2022
DOI: 10.3389/fendo.2022.842037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of In Vitro Maturation After Oocyte Retrieval With Gynecological Surgery for Refractory Polycystic Ovary Syndrome: A Retrospective Cohort Study

Abstract: ObjectiveTo explore the clinical outcomes of unstimulated in vitro maturation (IVM) after oocyte retrieval with gynecological surgery (IVM-surgery) for refractory polycystic ovary syndrome (PCOS) and analyze the influencing factors.MethodsPatients with refractory PCOS who underwent unstimulated IVM-surgery from June 2014 to September 2018 were included in this retrospective cohort study. Matured IVM oocytes were freshly fertilized and subsequently frozen at the blastocyst stage. Frozen-thawed embryo transfer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…73,74 Recently, it has been reported that a total of 93 women with refractory PCOS who underwent unstimulated IVM-surgery were included and the clinical outcomes were analyzed for the influencing factors, indicating that unstimulated IVM-surgery during laparoscopy and hysteroscopy procedures provided the opportunity for both spontaneous pregnancy and ART treatment. 75 Ovarian tissue cryopreservation is the primary method of fertility preservation for prepubertal girls who are at risk of premature ovarian failure (POF). Ovarian tissue cryopreservation followed by a transplant later may be offered as a method of fertility preservation for pubertal cancer patients who cannot receive ovarian stimulation due to time constraints or contraindications.…”
Section: Immature Oocytes From Ovarian Tissue or During Obstetric Gyn...mentioning
confidence: 99%
See 1 more Smart Citation
“…73,74 Recently, it has been reported that a total of 93 women with refractory PCOS who underwent unstimulated IVM-surgery were included and the clinical outcomes were analyzed for the influencing factors, indicating that unstimulated IVM-surgery during laparoscopy and hysteroscopy procedures provided the opportunity for both spontaneous pregnancy and ART treatment. 75 Ovarian tissue cryopreservation is the primary method of fertility preservation for prepubertal girls who are at risk of premature ovarian failure (POF). Ovarian tissue cryopreservation followed by a transplant later may be offered as a method of fertility preservation for pubertal cancer patients who cannot receive ovarian stimulation due to time constraints or contraindications.…”
Section: Immature Oocytes From Ovarian Tissue or During Obstetric Gyn...mentioning
confidence: 99%
“…IVM‐surgery has proposed transvaginal retrieval of immature oocytes during endoscopic gynecological procedures 73,74 . Recently, it has been reported that a total of 93 women with refractory PCOS who underwent unstimulated IVM‐surgery were included and the clinical outcomes were analyzed for the influencing factors, indicating that unstimulated IVM‐surgery during laparoscopy and hysteroscopy procedures provided the opportunity for both spontaneous pregnancy and ART treatment 75 …”
Section: Source Of Human Immature Oocytesmentioning
confidence: 99%
“…Second, the Welch t-test (26). The diagnosis of POEMS syndrome was confirmed based on the diagnostic criteria defined by Misawa et al (6). CIDP, chronic inflammatory demyelinating polyneuropathy; POEMS, polyneuropathy, organomegaly, endocrinopathy, M protein, skin changes.…”
Section: Machine Learningmentioning
confidence: 99%
“…Initially, there was a belief that the disease had a higher occurrence rate among individuals of Japanese descent, primarily based on initial reports from Japan (2,3). However, subsequent large series have been reported from France, the United States, China, and India (4)(5)(6)(7)(8). The diagnosis of POEMS syndrome in advanced stages with pathognomonic features is not always difficult.…”
Section: Introductionmentioning
confidence: 99%